Search for time-dependent CP violation in D0 → K+ K- and D0 → π+ π- decays - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Dziewiecki, Michal; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review, 2021)
A search for time-dependent violation of the charge-parity symmetry in D0→K+K− and D0→π+π− decays is performed at the LHCb experiment using proton-proton collision data recorded from 2015 to 2018 at a center-of-mass energy of 13 TeV, corresponding to an integrated luminosity of 6 fb−1. The D0 meson is required to originate from a D∗(2010)+→D0π+ decay, such that its flavor at production is identified by the charge of the accompanying pion. The slope of the time-dependent asymmetry of the decay rates of D0 and ¯D0 mesons into the final states under consideration is measured to be ΔYK+K−=(−2.3±1.5±0.3)×10−4, ΔYπ+π−=(−4.0±2.8±0.4)×10−4, where the first uncertainties are statistical and the second are systematic. These results are compatible with the conservation of the charge-parity symmetry at the level of 2 standard deviations and improve the precision by nearly a factor of 2.
LHCb Collaboration: R. Aaij, C. Abellán Beteta, T. Ackernley, B. Adeva, M. Adinolfi, H. Afsharnia, C.A. Aidala, S. Aiola, Z. Ajaltouni, S. Akar, J. Albrecht, F. Alessio, M. Alexander, A. Alfonso Albero, Z. Aliouche, G. Alkhazov, P. Alvarez Cartelle, S. Amato, Y. Amhis, L. An, L. Anderlini, A. Andreianov, M. Andreotti, F. Archilli, A. Artamonov, M. Artuso, K. Arzymatov, E. Aslanides, M. Atzeni, B. Audurier, S. Bachmann, M. Bachmayer, J.J. Back, S. Baker, P. Baladron Rodriguez, V. Balagura, W. Baldini, J. Baptista Leite, R.J. Barlow, S. Barsuk, W. Barter, M. Bartolini, F. Baryshnikov, J.M. Basels, G. Bassi, B. Batsukh, A. Battig, A. Bay, M. Becker, F. Bedeschi, I. Bediaga, A. Beiter, V. Belavin, S. Belin, V. Bellee, K. Belous, I. Belov, I. Belyaev, G. Bencivenni, E. Ben-Haim, A. Berezhnoy, R. Bernet, D. Berninghoff, H.C. Bernstein, C. Bertella, A. Bertolin, C. Betancourt, F. Betti, Ia. Bezshyiko, S. Bhasin, J. Bhom, L. Bian, M.S. Bieker, S. Bifani, P. Billoir, M. Birch, F.C.R. Bishop, A. Bitadze, A. Bizzeti, M. Bjørn, M.P. Blago, T. Blake, F. Blanc, S. Blusk, D. Bobulska, J.A. Boelhauve, O. Boente Garcia, T. Boettcher, A. Boldyrev, A. Bondar, N. Bondar, S. Borghi, M. Borisyak, M. Borsato, J.T. Borsuk, S.A. Bouchiba, T.J.V. Bowcock, A. Boyer, C. Bozzi, M.J. Bradley, S. Braun, A. Brea Rodriguez, M. Brodski, J. Brodzicka, A. Brossa Gonzalo, D. Brundu, A. Buonaura, C. Burr, A. Bursche, A. Butkevich, J.S. Butter, J. Buytaert, W. Byczynski, S. Cadeddu, H. Cai, R. Calabrese, L. Calefice, L. Calero Diaz, S. Cali, R. Calladine, M. Calvi, M. Calvo Gomez, P. Camargo Magalhaes, A. Camboni, P. Campana, A.F. Campoverde Quezada, S. Capelli, L. Capriotti, A. Carbone, G. Carboni, R. Cardinale, A. Cardini, I. Carli, P. Carniti, L. Carus, K. Carvalho Akiba, A. Casais Vidal, G. Casse, M. Cattaneo, G. Cavallero, S. Celani, J. Cerasoli, A.J. Chadwick, M.G. Chapman, M. Charles, Ph. Charpentier, G. Chatzikonstantinidis, C.A. Chavez Barajas, M. Chefdeville, C. Chen, S. Chen, A. Chernov, V. Chobanova, S. Cholak, M. Chrzaszcz, A. Chubykin, V. Chulikov, P. Ciambrone, M.F. Cicala, X. Cid Vidal, G. Ciezarek, P.E.L. Clarke, M. Clemencic, H.V. Cliff, J. Closier, J.L. Cobbledick, V. Coco, J.A.B. Coelho, J. Cogan, E. Cogneras, L. Cojocariu, P. Collins, T. Colombo, L. Congedo, A. Contu, N. Cooke, G. Coombs, G. Corti, C.M. Costa Sobral, B. Couturier, D.C. Craik, J. Crkovská, M. Cruz Torres, R. Currie, C.L. Da Silva, E. Dall’Occo, J. Dalseno, C. D’Ambrosio, A. Danilina, P. d’Argent, A. Davis, O. De Aguiar Francisco, K. De Bruyn, S. De Capua, M. De Cian, J.M. De Miranda, L. De Paula, M. De Serio, D. De Simone, P. De Simone, J.A. de Vries, C.T. Dean, D. Decamp, L. Del Buono, B. Delaney, H.-P. Dembinski, A. Dendek, V. Denysenko, D. Derkach, O. Deschamps, F. Desse, F. Dettori, B. Dey, P. Di Nezza, S. Didenko, L. Dieste Maronas, H. Dijkstra, V. Dobishuk, A.M. Donohoe, F. Dordei, A.C. dos Reis, L. Douglas, A. Dovbnya, A.G. Downes, K. Dreimanis, M.W. Dudek, L. Dufour, V. Duk, P. Durante, J.M. Durham, D. Dutta, M. Dziewiecki, A. Dziurda, A. Dzyuba, S. Easo, U. Egede, V. Egorychev, S. Eidelman, S. Eisenhardt, S. Ek-In, L. Eklund, S. Ely, A. Ene, E. Epple, S. Escher, J. Eschle, S. Esen, T. Evans, A. Falabella, J. Fan, Y. Fan, B. Fang, S. Farry, D. Fazzini, P. Fedin, M. Féo, P. Fernandez Declara, A. Fernandez Prieto, J.M. Fernandez-tenllado Arribas, F. Ferrari, L. Ferreira Lopes, F. Ferreira Rodrigues, S. Ferreres Sole, M. Ferrillo, M. Ferro-Luzzi, S. Filippov, R.A. Fini, M. Fiorini, M. Firlej, K.M. Fischer, C. Fitzpatrick, T. Fiutowski, F. Fleuret, M. Fontana, F. Fontanelli, R. Forty, V. Franco Lima, M. Franco Sevilla, M. Frank, E. Franzoso, G. Frau, C. Frei, D.A. Friday, J. Fu, Q. Fuehring, W. Funk, E. Gabriel, T. Gaintseva, A. Gallas Torreira, D. Galli, S. Gambetta, Y. Gan, M. Gandelman, P. Gandini, Y. Gao, M. Garau, L.M. Garcia Martin, P. Garcia Moreno, J. García Pardiñas, B. Garcia Plana, F.A. Garcia Rosales, L. Garrido, C. Gaspar, R.E. Geertsema, D. Gerick, L.L. Gerken, E. Gersabeck, M. Gersabeck, T. Gershon, D. Gerstel, Ph. Ghez, V. Gibson, H.K. Giemza, M. Giovannetti, A. Gioventù, P. Gironella Gironell, L. Giubega, C. Giugliano, K. Gizdov, E.L. Gkougkousis, V.V. Gligorov, C. Göbel, E. Golobardes, D. Golubkov, A. Golutvin, A. Gomes, S. Gomez Fernandez, F. Goncalves Abrantes, M. Goncerz, G. Gong, P. Gorbounov, I.V. Gorelov, C. Gotti, E. Govorkova, J.P. Grabowski, R. Graciani Diaz, T. Grammatico, L.A. Granado Cardoso, E. Graugés, E. Graverini, G. Graziani, A. Grecu, L.M. Greeven, P. Griffith, L. Grillo, S. Gromov, B.R. Gruberg Cazon, C. Gu, M. Guarise, P.A. Günther, E. Gushchin, A. Guth, Y. Guz, T. Gys, T. Hadavizadeh, G. Haefeli, C. Haen, J. Haimberger, T. Halewood-leagas, P.M. Hamilton, Q. Han, X. Han, T.H. Hancock, S. Hansmann-Menzemer, N. Harnew, T. Harrison, C. Hasse, M. Hatch, J. He, M. Hecker, K. Heijhoff, K. Heinicke, A.M. Hennequin, K. Hennessy, L. Henry, J. Heuel, A. Hicheur, D. Hill, M. Hilton, S.E. Hollitt, J. Hu, J. Hu, W. Hu, W. Huang, X. Huang, W. Hulsbergen, R.J. Hunter, M. Hushchyn, D. Hutchcroft, D. Hynds, P. Ibis, M. Idzik, D. Ilin, P. Ilten, A. Inglessi, A. Ishteev, K. Ivshin, R. Jacobsson, S. Jakobsen, E. Jans, B.K. Jashal, A. Jawahery, V. Jevtic, M. Jezabek, F. Jiang, M. John, D. Johnson, C.R. Jones, T.P. Jones, B. Jost, N. Jurik, S. Kandybei, Y. Kang, M. Karacson, M. Karpov, N. Kazeev, F. Keizer, M. Kenzie, T. Ketel, B. Khanji, A. Kharisova, S. Kholodenko, K.E. Kim, T. Kirn, V.S. Kirsebom, O. Kitouni, S. Klaver, K. Klimaszewski, S. Koliiev, A. Kondybayeva, A. Konoplyannikov, P. Kopciewicz, R. Kopecna, P. Koppenburg, M. Korolev, I. Kostiuk, O. Kot, S. Kotriakhova, P. Kravchenko, L. Kravchuk, R.D. Krawczyk, M. Kreps, F. Kress, S. Kretzschmar, P. Krokovny, W. Krupa, W. Krzemien, W. Kucewicz, M. Kucharczyk, V. Kudryavtsev, H.S. Kuindersma, G.J. Kunde, T. Kvaratskheliya, D. Lacarrere, G. Lafferty, A. Lai, A. Lampis, D. Lancierini, J.J. Lane, R. Lane, G. Lanfranchi, C. Langenbruch, J. Langer, O. Lantwin, T. Latham, F. Lazzari, R. Le Gac, S.H. Lee, R. Lefèvre, A. Leflat, S. Legotin, O. Leroy, T. Lesiak, B. Leverington, H. Li, L. Li, P. Li, Y. Li, Y. Li, Z. Li, X. Liang, T. Lin, R. Lindner, V. Lisovskyi, R. Litvinov, G. Liu, H. Liu, S. Liu, X. Liu, A. Loi, J. Lomba Castro, I. Longstaff, J.H. Lopes, G.H. Lovell, Y. Lu, D. Lucchesi, S. Luchuk, M. Lucio Martinez, V. Lukashenko, Y. Luo, A. Lupato, E. Luppi, O. Lupton, A. Lusiani, X. Lyu, L. Ma, S. Maccolini, F. Machefert, F. Maciuc, V. Macko, P. Mackowiak, S. Maddrell-Mander, O. Madejczyk, L.R. Madhan Mohan, O. Maev, A. Maevskiy, D. Maisuzenko, M.W. Majewski, J.J. Malczewski, S. Malde, B. Malecki, A. Malinin, T. Maltsev, H. Malygina, G. Manca, G. Mancinelli, R. Manera Escalero, D. Manuzzi, D. Marangotto, J. Maratas, J.F. Marchand, U. Marconi, S. Mariani, C. Marin Benito, M. Marinangeli, P. Marino, J. Marks, P.J. Marshall, G. Martellotti, L. Martinazzoli, M. Martinelli, D. Martinez Santos, F. Martinez Vidal, A. Massafferri, M. Materok, R. Matev, A. Mathad, Z. Mathe, V. Matiunin, C. Matteuzzi, K.R. Mattioli, A. Mauri, E. Maurice, J. Mauricio, M. Mazurek, M. McCann, L. Mcconnell, T.H. Mcgrath, A. McNab, R. McNulty, J.V. Mead, B. Meadows, C. Meaux, G. Meier, N. Meinert, D. Melnychuk, S. Meloni, M. Merk, A. Merli, L. Meyer Garcia, M. Mikhasenko, D.A. Milanes, E. Millard, M. Milovanovic, M.-N. Minard, L. Minzoni, S.E. Mitchell, B. Mitreska, D.S. Mitzel, A. Mödden, R.A. Mohammed, R.D. Moise, T. Mombächer, I.A. Monroy, S. Monteil, M. Morandin, G. Morello, M.J. Morello, J. Moron, A.B. Morris, A.G. Morris, R. Mountain, H. Mu, F. Muheim, M. Mukherjee, M. Mulder, D. Müller, K. Müller, C.H. Murphy, D. Murray, P. Muzzetto, P. Naik, T. Nakada, R. Nandakumar, T. Nanut, I. Nasteva, M. Needham, I. Neri, N. Neri, S. Neubert, N. Neufeld, R. Newcombe, T.D. Nguyen, C. Nguyen-Mau, E.M. Niel, S. Nieswand, N. Nikitin, N.S. Nolte, C. Nunez, A. Oblakowska-Mucha, V. Obraztsov, D.P. O’Hanlon, R. Oldeman, M.E. Olivares, C.J.G. Onderwater, A. Ossowska, J.M. Otalora Goicochea, T. Ovsiannikova, P. Owen, A. Oyanguren, B. Pagare, P.R. Pais, T. Pajero, A. Palano, M. Palutan, Y. Pan, G. Panshin, A. Papanestis, M. Pappagallo, L.L. Pappalardo, C. Pappenheimer, W. Parker, C. Parkes, C.J. Parkinson, B. Passalacqua, G. Passaleva, A. Pastore, M. Patel, C. Patrignani, C.J. Pawley, A. Pearce, A. Pellegrino, M. Pepe Altarelli, S. Perazzini, D. Pereima, P. Perret, K. Petridis, A. Petrolini, A. Petrov, S. Petrucci, M. Petruzzo, T.T.H. Pham, A. Philippov, L. Pica, M. Piccini, B. Pietrzyk, G. Pietrzyk, M. Pili, D. Pinci, F. Pisani, A. Piucci, Resmi P. K, V. Placinta, J. Plews, M. Plo Casasus, F. Polci, M. Poli Lener, M. Poliakova, A. Poluektov, N. Polukhina, I. Polyakov, E. Polycarpo, G.J. Pomery, S. Ponce, D. Popov, S. Popov, S. Poslavskii, K. Prasanth, L. Promberger, C. Prouve, V. Pugatch, H. Pullen, G. Punzi, W. Qian, J. Qin, R. Quagliani, B. Quintana, N.V. Raab, R.I. Rabadan Trejo, B. Rachwal, J.H. Rademacker, M. Rama, M. Ramos Pernas, M.S. Rangel, F. Ratni...
Im Titel sind die Zahl Null "0", das Pluszeichen "+" und das Minuszeichen "-" jeweils hochgestellt
Gesehen am 16.05.2022